Conversion to Open Surgery in Laparoscopic Colorectal Cancer Resection: Predictive Factors and its Impact on Long-Term Outcomes. A Case Series Study. Issue 1 (9th February 2022) - Baixauli, Jorge; Cienfuegos, Javier A.; Martinez Regueira, Fernando; Pastor, Carlos; Justicia, Carlos S.; Valentí, Víctor; Rotellar, Fernando; Hernández Lizoáin, José L.
Abstract : Background: Laparoscopic resection is the treatment of choice for colorectal cancer. Rates of conversion to open surgery range between 7% and 30% and controversy exists as to the effect of this on oncologic outcomes. The objective of this study was to analyze what factors are predictive of conversion and what effect they have on oncologic outcomes. Methods: From a prospective database of patients undergoing laparoscopic surgery between 2000 and 2018 a univariate and multivariate analyses were made of demographic, pathologic, and surgical variables together with complementary treatments comparing purely laparoscopic resection with conversions to open surgery. Overall and disease-free survival were compared using the Kaplan-Meier method. Results: Of a total of 829 patients, 43 (5.18%) converted to open surgery. In the univariate analysis, 12 variables were significantly associated with conversion, of which left-sided resection [odds ratio (OR): 2.908; P =0.02], resection of the rectum (OR: 4.749, P =0.014), and local invasion of the tumor (OR: 6.905, P <0.01) were independently predictive factors in the multiple logistic regression. Female sex was associated with fewer conversions (OR: 0.375, P =0.012). The incidence and pattern of relapses were similar in both groups and there were no significant differences between overall and disease-free survival. Conclusions: Left-sided resections, resections of the rectum and tumor invasion of neighboring structures are associated with higher rates of conversion. Female sex is associated with fewer conversions. Conversion to open surgery does not compromise oncologic outcomes at 5 and 10 years.